Mimicking portfolios with conditioning information - Ferson, Wayne E. 1951-; Siegel, Andrew F. 1950-; Xu, Pisun (National Bureau of Economic Research, 2005)
"Mimicking portfolios have long been useful in asset pricing research. In most empirical applications, the portfolio weights are assumed to be fixed over time, while in theory they may be functions of the economic state. This paper derives and characterizes mimicking portfolios in the presence of predetermined state variables, or conditioning information. The results generalize and integrate multifactor minimum variance efficiency (Fama, 1996) with conditional and unconditional mean variance efficiency (Hansen and Richard (1987), Ferson and Siegel, 2001). Empirical examples illustrate the potential importance of time-varying mimicking portfolio weights and highlight challenges in their application"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Stocks -- Econometric models